Proposal and Validation of a Novel Scoring System for Hepatocellular Carcinomas Beyond Curability Borders - DEMİRTAŞ, COŞKUN ÖZER; DULUNDU, ENDER; GÜNDÜZ, FEYZA; BALTACIOĞLU, FEYYAZ; ÖZDOĞAN, OSMAN CAVİT; YUMUK, PERRAN FULDEN (JOHN WILEY & SONS LTD, 2022)
Optimal scoring system for clinical prognostic factors in patients with unresectable hepatocellular carcinoma (HCC) is currently uncertain. We aimed to develop and externally validate an easy to use tool, particularly for this population, and named it the unresectable hepatocellular carcinoma prognostic index (UHPI). We evaluated the data of patients with treatment-naive unresectable HCC who were diagnosed in the training center from 2010 to 2019 (n = 209). A simple prognostic model was developed by assigning points for each covariate in proportion to the beta coefficients in the Cox multivariable model. Predictive performance and distinction ability of the UHPI were further evaluated in an independent European validation cohort (n = 147) and compared with 11 other available models. A simple scoring system was derived, assigning 0.5/1/2 scores for six independent covariates including, the Child-Pugh score, Eastern Cooperative Oncology Group performance status, maximum tumor size, vascular invasion or extrahepatic metastasis, lymph node involvement, and alpha-fetoprotein. The UHPI score, ranging from 0 to 6, showed superior performance in prognosis prediction and outperformed 11 other staging or prognostic models, giving the highest homogeneity (c-index, 6-month and 1-year area under the receiver operator characteristic curves), lowest Akaike information criterion, and -2 log-likelihood ratio values. The UHPI score allocated well the risk of patients with unresectable HCC for mortality within the first year, using two cut-off values (low-risk, <0.5; intermediate-risk, 0.5-2; high-risk, >2). Conclusion: The UHPI score can predict prognosis better than other systems in subjects with unresectable HCC and can be used in clinical practice or trials to estimate the 6-month and 1-year survival probabilities for this group.
Keywords: PERCUTANEOUS THERMAL ABLATION; STAGING-SYSTEM; ESTIMATE SURVIVAL; PROGNOSIS; SORAFENIB; MODEL; CHEMOEMBOLIZATION; STRATIFICATION; MANAGEMENT; MICROWAVE